Peningkatan Kemampuan Motorik Halus melalui Bermain Kertas Krep di Taman Kanak-kanak - Yenti, Gusni; Mayar, Farida; Mahyuddin, Nenny (Penerbit Aksara Rentaka Siar (ARS), 2019)
The research aims to improve the fine motor skills of early childhood in kindergarten Aisyiyah Bustanul Atfha 15 Padang. The type research conducted was classroom action research involving an observation on designed activities in the classroom. The tehnique of data analysis was qualitative which was condcted from the students result using percentage approach. In the first cycle of meeting theree, children’s file motor skills reached thirty four percent and had yet attain the minimum completion criteria. Meanwhile, in the second cycle of meeting three, children’s fine motor skills have significantly improved to eighty three percent and attained the minimum completion criteria. Finding showed that activity using crepe papaer has improved childrean’s fine motor skills in kindergarten Aisyiyah Bustanul Atfhal 15 Padang.